2022
DOI: 10.3390/en15031000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electricity and Natural Gas Security. A Case Study for Germany, France, Italy and Spain

Abstract: This work aims to present an analysis of electricity and natural gas supply security in the four European Union countries with the highest level of consumption, namely Germany, France, Italy, and Spain. The goal of the study is to use and adapt a set of 22 indicators for estimating the level of energy security. The evaluation of an index called “Energy Security Level”, measuring the overall energy security, is performed for the period 2006–2018 in order to compare its evolution in each of the analyzed countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Unlike the English network, many "nucléaire" appeared in the French network, which was related to the current situation of French nuclear power plants. Studies have shown that France has many nuclear power plants to make it resilient in energy security (Krikštolaitis et al, 2022). However, as half of the nuclear power plants are approaching the end of their design life, the energy problem in France is becoming increasingly prominent.…”
Section: Sentiment Comparison Of English and French Tweetsmentioning
confidence: 99%
“…Unlike the English network, many "nucléaire" appeared in the French network, which was related to the current situation of French nuclear power plants. Studies have shown that France has many nuclear power plants to make it resilient in energy security (Krikštolaitis et al, 2022). However, as half of the nuclear power plants are approaching the end of their design life, the energy problem in France is becoming increasingly prominent.…”
Section: Sentiment Comparison Of English and French Tweetsmentioning
confidence: 99%
“…This explains the European Commission's growing concern to increase the energy security of the EU. Many studies show that this security varies throughout the EU [21,22]. For example, countries in the western European region (e.g., Germany and France) have higher energy security than southern Europe (e.g., Italy and Spain), primarily due to the more developed infrastructure and a richer energy mix.…”
Section: Introductionmentioning
confidence: 99%
“…The latest literature on energy security and natural gas is rich and covers a variety of issues. For example, index approach to energy security is presented in [31], where the evaluation of an index called "Energy Security Level", measuring the overall energy security, is performed. The index assessing energy security is also covered in [32,33].…”
Section: Introductionmentioning
confidence: 99%